2013
DOI: 10.1186/2045-3701-3-1
|View full text |Cite|
|
Sign up to set email alerts
|

The MTA family proteins as novel histone H3 binding proteins

Abstract: BackgroundThe nucleosome remodeling and histone deacetylase complex (Mi2/NRD/NuRD/NURD) has a broad role in regulation of transcription, DNA repair and cell cycle. Previous studies have revealed a specific interaction between NURD and histone H3N-terminal tail in vitro that is not observed for another HDAC1/2-containing complex, Sin3A. However, the subunit(s) responsible for specific binding of H3 by NURD has not been defined.ResultsIn this study, we show among several class I HDAC-containing corepressor compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 55 publications
6
21
0
Order By: Relevance
“…Earlier our group also reported significant iNOS inihibition in lung tissues of irradiated mice by our previously derived formulation [18]. In line with our observation, other agents like Aminoguanidine [36], 17-dimethylamino-ethylamino-17-demethoxygeldanamycin (17-DMAG) [37] have been reported for their radioprotective ability in intestine, blood and bone marrow of mice mainly through inhibition of iNOS.…”
Section: Discussionsupporting
confidence: 86%
“…Earlier our group also reported significant iNOS inihibition in lung tissues of irradiated mice by our previously derived formulation [18]. In line with our observation, other agents like Aminoguanidine [36], 17-dimethylamino-ethylamino-17-demethoxygeldanamycin (17-DMAG) [37] have been reported for their radioprotective ability in intestine, blood and bone marrow of mice mainly through inhibition of iNOS.…”
Section: Discussionsupporting
confidence: 86%
“…The MTA2 protein is acetylated at lysine 152 by p300 histone acetylase enzyme (Zhou et al, 2014). In addition, functions of MTA proteins are influenced by the ability of MTA 1 and MTA2 to interact with histone H3 and chromatin remodeling components (Nair, et al, 2013; Wu et al, 2013). …”
Section: Basis Of Functionality Of Mta Proteinsmentioning
confidence: 99%
“…The MTA1 also interact with the histone H3 tail, but this interaction is dispensable for the association of the NuRD complex with chromatin [60]. Interestingly, an esophageal carcinomas based biomarker study demonstrated an inverse relationship between the levels of MTA1 upregulation and acetylation status of histone H4 [61].…”
Section: Global Mta1-nucleosome Interactionsmentioning
confidence: 99%